(3MGTjI Ydi MGTjI JgPjH GdefWbs - (3LeGd GdOjf eMeO GdNhfSGQjs ((3LeGd GdOjf Hf Ydj NGfs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bhdg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI gcPG hLO YHGQI GdeJf aj GdcKjQ ef GdfSN hGdUhGH Gf daXgG ggfG RGFOI haYJ SghG ef bde GdfGSN (B...s
(3BNQgG (B:s
... (3Ydi ZjQ GdMhGS bjGSG Ydi GdMhGS hbHd cd ehLhO (B... (3dGfg GdehUd Edi GdJUOjb GdcGedI GdJj hUdJ Edi eQJHI Gdjbjf hfNJe cJGHfGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs